Software development for fluid flow visualization using computer graphics and animation techniques. - Liongson, Leonardo Q. (Philippine Engineering Journal)
This paper presents the principal results of a two year software development project for the visualization of fluid motion using computer graphics and animation techniques. Twenty five (25) visualization programs have been developed for potential flows, viscous flows, flows with heat and mass transfer, geostrophic flows and open channel flows. Single page and double page animation and palette rotation (neon-light effect), featuring on the monitor screen the display of both text and graphics with color, animation and sound are the essential techniques utilized. Classical tools in engineering mathematics were numerically applied and implemented, such as complex variable theory, conformal mapping, both analytical and numerical solutions of ordinary and partial differential equations, and stochastic or random walk simulation of the diffusion process. The applied techniques (computer graphics, animation, analytical and numerical methods in engineering mathematics) exhibited varying degrees of performance in terms of a meaningful perception of fluid motion, depending on appropriateness of the application to certain types of flows and on the nature and amount of detail present in the images. With the added features of a simple and guided input menu, a facility for instant replay, and a real time mode of computation and display, the programs serve as interactive teaching tools in fluid mechanics.